A Candle Light for Enhancing Employee Engagement and Quality Customer Service - Limsatitpong, Palakorn (ABAC ODI JOURNAL Vision. Action. Outcome, 2014)
No Abstract First of all, I would like to express my gratitude to Assumption University, Master of Management in Organization Development (MMOD) Faculty members, my beloved MMOD teachers, my company and colleagues from Toyota Motor Thailand and Bro. Martin Prathip Komalmas for giving me an opportunity to propose my action research thesis. My action research thesis has a title of “Enhancing Employee Engagement and Quality Customer Service”. The action research was not only encourage me to contribute organizational development to my company but also be a candle light to guide me for self and career development and a way to live my future life as dream.